Kepemimpinan Kepala Sekolah Menuju Pembelajaran Abad 21 - Salmia Salmia; Rosleny Rosleny; Idawati Idawati (Universitas Pendidikan Indonesia (UPI), 2020)
AbstractThe improvement of school education quality is determined by the ability of headmaster in empowering the teaching staffs and the community member as a whole. This study aims to determine the steps performed by the headmaster in improving the teachers’ professionalism toward the 21st century learning. This study design was qualitative descriptive. Data were collected through interview, observation and documentation. This study used data analysis techniques which consisted of several stages: data collection, data reduction, data presentation and drawing a conclusion. This study result toward the leadership of headmaster in improving the teachers’ professionalism was the steps performed by headmaster such as: involving teachers in participating the technical guidance (Bimtek), Workshop, Teacher Working Group, seminars, Education and Training, and supervision which motivate teachers to always work in accordance with their respective duties with expertise according to their profession, and in those activities, the teachers are expected to improve their professionalism. The factors which hampered the headmaster in improving the teachers’ professionalism toward the 21st century learning were the lack of facilities and infrastructures, the lack of teachers’ knowledge in operating the computer, the teachers’ teach the lessons which are not in accordance with their program, discipline and good cooperation between school staffs. The conclusion of this study was the headmaster with full responsibility improving the teachers’ professionalism toward the 21st century learning. AbstrakPeningkatan Mutu Pendidikan sekolah ditentukan oleh kemampuan kepala sekolah dalam memberdayakan staf pengajar dan anggota komunitasnya secara keseluruhan. Tujuan penelitian ini untuk mengetahui tentang langkah-langkah yang dilakukan kepala sekolah dalam meningkatkan profesionalisme guru menuju pembelajaran abad 21 serta kendala-kendala kepala sekolah dalam meningkatkan profesionalisme guru menuju pembelajaran abad 21. Penelitian ini menggunakan deskriptif kualitatif. Data dikumpulkan melalui wawancara, observasi dan dokumentasi. Penelitian ini menggunakan teknik analisa data, yang terdiri dari tahap pengumpulan data, reduksi data, sajian data dan penarikan simpulan. Hasil penelitian terhadap kepemimpinan kepala sekolah dalam meningkatkan profesionalisme guru adalah langkah-langkah yang dilakukan kepala sekolah untuk meningkatkan profesionalisme guru yaitu dengan mengikutsertakan guru dalam mengikuti kegiatan Bimbingan teknis (Bimtek), Workshoap, Kelompok Kerja Guru (KKG), seminar, Diklat, dan supervisi yang dapat memberikan motivasi pada guru untuk selalu bekerja sesuai dengan tugasnya masing-masing dengan keahlian yang sesuai profesinya, dalam kegiatan tersebut guru dapat lebih meningkatkan keprofesionalnnya. Adapun faktor yang menjadi kendala kepala sekolah dalam meningkatkan profesionalisme guru menuju pembelajaran abad 21 adalah kurangnya sarana dan prasarana, masih minimnya pengetahuan guru dalam pengaplikasian komputer, guru mengajarkan pelajaran yang tidak sesuai dengan program, kedisiplinan dan juga kerjasama yang baik antar pihak sekolah. Kesimpulan dari penelitian ini adalah kepala sekolah dengan penuh tanggung jawab dalam meningkatkan profesionalisme guru menuju pembelajaran abad 21.